PROFIT SHARING PRACTICE IN MUKHABARAH CONTRACT ACCORDING TO FIQIH MUAMALAH (CASE STUDY IN SENDANG VILLAGE, JAMBON DISTRICT, PONOROGO REGENCY) - Zulfatus Sa'diah; Muhamad Syamsul Huda (Universitas Islam Negeri Mataram, 2022)
Cooperation with the mukhabarah contract profit sharing system is one of the muamalah activities that often occurs among the Indonesian people, especially in the agricultural sector and it involves two parties, namely the land owner and also the land cultivator. This study aims to determine the practice of agricultural production sharing in mukhabarah contracts and a review of muamalah fiqh on these practices. The results of this study indicate that the contract is carried out verbally with the provision of seeds and all cultivation capital is borne by the land cultivator, while for the distribution of the results it is divided by mertelu or 1/3 between the land owner and the cultivator. If it is reviewed in muamalah fiqh, the practice of the mukhabarah contract is appropriate, However, there is an element that is contrary to the conditions for mukhabarah, namely in the distribution of the harvest the results are not weighed first, only based on the number of sacks, each bag is filled with 3 baskets of harvest, the scales of which are not clear. So that there is an element of gharar and contains an element of injustice that results in disputes between land owners and land cultivators.